Sanksi Kode Etik bagi Notaris yang tidak Menjalankan Kewajiban Jabatannya - Nadia Fauziah Anugrah; Suwari Akhmaddhian (Universitas Kuningan, 2020)
The purpose of this paper is to analyze the meaning of certain reasons in the Notary Ethics Code, related to the obligation to carry out positions in his office and the consequences of violating these provisions on the authenticity of the deed. The method used is a normative juridical method with a statutory approach and a conceptual approach. The results of the study indicate that the meaning of